An expert system for the diagnosis of irritable bowel syndrome - SURDEA-BLAGA, TEODORA (Clujul Med, 2013)
For a long time functional digestive disorders (FGIDs), including irritable bowel syndrome (IBS), were described based on what they are not, without considering them real entities. Although IBS evolution is benign, it has major effects on the quality of life, it determines a higher number of days of sick leave or days when work activities had to be interrupted, thus increasing the expenses for the society. Our system, developed using CORVID Exsys, is called IBS Expert and addresses both patients and physicians. Answering some simple questions, patients will receive information about their diagnosis, together with additional recommendations. Non-expert physicians will have rapid access to the algorithm of IBS diagnosis, and could use recommendations for future investigations. This expert system is based on the information provided by the most complete collection of data about FGIDs, created by an international group of experts, who elaborated Rome III criteria. The system consists of three sub-systems, including a set of eighteen questions and the diagnosis of IBS, as well as additional recommendations, established using confidence variables. The evaluation of the system consisted of verification (determining the accuracy of the results to ensure the delivery of diagnosis and recommendations as it was intended), validation of knowledge (met through the use of the gold standard in the field) and assessment of the impact on users, either patients or physicians (measuring overall satisfaction and the user effort score in using the system). The system is available online at www.gastroterra.ro and can be accessed by using any Java-enabled device, from standard computers to mobile devices.